Quantitative analysis of feeding kitchen food waste to domestic animals in rural and semi-urban areas from Sammanthurai Divisional Secretariat Division in Sri Lanka - Mohamed G. Mohamed Thariq; Mohamed I. Mufassara; Mohamed M. Mohamed Najim (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: Some literature on feeding kitchen food waste (KFW) to domestic animals is available. However, the quantification of such consumption by those animals is limited. This study attempts to investigate how various domestic animals contribute to disposing of the KFW by feeding in rural and semi-urban areas of the eastern province of Sri Lanka.